2016
DOI: 10.1016/j.gca.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Temperature calibration and phylogenetically distinct distributions for freshwater alkenones: Evidence from northern Alaskan lakes

Abstract: Alkenones are a class of unsaturated long-chain ketone biomarkers that have been used to reconstruct sea surface temperature and, more recently, continental temperature, by way of alkenone unsaturation indices (e.g. and). Alkenones are frequently found in brackish and saline lakes, however species effects confound temperature reconstructions when multiple alkenone-producing species with different temperature responses are present. Interestingly, available genetic data indicate that numerous freshwater lakes ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
156
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(162 citation statements)
references
References 61 publications
6
156
0
Order By: Relevance
“…Interestingly, Richmond and Deadmoose lakes each contained two main LCA‐producing haptophyte species, while the other studied lakes only contained a single dominant LCA‐haptophyte species. These results are consistent with previous studies that have shown that Group I haptophytes only occur in freshwater and oligohaline lakes, whereas Group II haptophytes occur in oligohaline to hyperhaline lakes (Longo et al, , ; Plancq, McColl, et al, ; Simon et al, ; Theroux et al, ; Toney et al, ). When looking at the LCA profiles (Figure ), OTU_21 is associated with a LCA profile with tri‐unsaturated isomers and the presence of C 38 Me LCAs, which has been shown to be characteristic of Group I haptophytes (Longo et al, , ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, Richmond and Deadmoose lakes each contained two main LCA‐producing haptophyte species, while the other studied lakes only contained a single dominant LCA‐haptophyte species. These results are consistent with previous studies that have shown that Group I haptophytes only occur in freshwater and oligohaline lakes, whereas Group II haptophytes occur in oligohaline to hyperhaline lakes (Longo et al, , ; Plancq, McColl, et al, ; Simon et al, ; Theroux et al, ; Toney et al, ). When looking at the LCA profiles (Figure ), OTU_21 is associated with a LCA profile with tri‐unsaturated isomers and the presence of C 38 Me LCAs, which has been shown to be characteristic of Group I haptophytes (Longo et al, , ).…”
Section: Discussionsupporting
confidence: 92%
“…Richmond Lake displayed a predominance of C 38 alkenones over C 37 alkenones, with particularly elevated concentrations of the C 38:3 alkenone. Finally, Lenore Lake showed the presence of tri‐unsaturated alkenone isomers, including the C 37:3b isomer, which has been shown to be characteristic of the Group I of LCA‐producing haptophytes (Dillon et al, ; Longo et al, , , ). Total concentrations of LCAs ranged from 12.9 to 2,184 μg/g dry sediment, with the highest concentrations (>1,000 μg/g dry sediment) recorded in Manitou and Middle lakes (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkenone production is restricted to haptophyte algae in the order Isochrysidales and alkenone‐producing species have been categorized into three main groups based on phylogenetic relationships and commonly associated habitats (Theroux et al ; Longo et al ). Group I alkenone‐producing haptophytes (hereafter, Group I) have been found in fresh and oligohaline lakes (Theroux et al ; Simon et al ; Longo et al ), and are believed to only occupy environments with salinities lower than ~ 5 psu (Longo et al ). Group II alkenone‐producing haptophytes (Group II) are common in brackish and saline lakes and coastal environments, and Group III alkenone‐producing haptophytes (Group III) are common in open ocean marine environments (Theroux et al ; Longo et al ).…”
mentioning
confidence: 99%
“…A narrow phylogenetic range in marine alkenone‐producers allows for the application of a universal U37K' calibration for sea surface temperature reconstructions, a calibration that was first developed empirically through culture work (Brassell et al ; Prahl and Wakeham ) and later validated with a global core‐top survey (Müller et al ; Conte et al ). For freshwater environments where Group I haptophytes have been identified, namely a series of arctic lakes in Greenland (D'Andrea et al ) and Alaska (Longo et al ), studies have found a uniform species occurrence that allows for a consistent temperature calibration to be applied in individual lakes. In Lake BrayaSø, Greenland, for example, an in situ U37K calibration derived from a single haptophyte species matched a downcore alkenone profile spanning 6000 yr (Theroux et al , ; D'Andrea et al ).…”
mentioning
confidence: 99%